Driving Empathy on Social Media: Factors Influencing Empathy Expression on the Ministry of Education Brunei’s Instagram - Anis Nadiah Azry; Syahirah Suhaili (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2026)
This research evaluates the factors that influence individuals’ intention to express empathy towards educational information disseminated via the Ministry of Education (MOE) Brunei’s Instagram account. This research specifically investigates the influence of perceived informativeness, credibility, creativity, and attitude towards empathy expression on users’ intention to express empathy. A quantitative research method was applied, using an online survey questionnaire developed with Google Forms. The survey was circulated via WhatsApp and Outlook email, which successfully achieved 160 responses. The data collected were then analysed using the Statistical Package for the Social Sciences (SPSS) through reliability analysis, Pearson correlation, simple scatterplot, and linear regression analysis. The findings showed that all four variables positively and significantly influenced intention to express empathy. Out of all variables, attitude towards empathy expression emanated as the strongest predictor. These results show that users are more inclined to express empathy to educational information when they perceive the content delivered as informative, credible, creative, and if they hold favourable attitudes towards empathy expression. Furthermore, this research contributes to the growing literature on social media communication by offering evidence from Brunei Darussalam, confirming that informativeness, credibility, creativity, and attitude towards empathy expression influence individuals’ intention to express empathy towards educational information on Instagram. In addition, the findings recommend that MOE Brunei focus on fostering positive attitudes towards empathy expression, alongside creating informative, credible, and creative content, to encourage greater engagement with educational messages on social media.